Determinants for Disease Management in Cacao (Theobroma cacao L.) in Southern Córdoba, Colombia (2023)
The southern region of Córdoba has included the cultivation of cocoa within the offer of agricultural products for about two decades, motivated by the action of public and private entities in the agricultural sector. Although their yields are very close to the national average, they have decreased in the last two years due to diseases. This work aims to identify the factors that influence the decision to use disease management technologies. A survey was applied to 158 producers selected by the simple random sampling method. For the analysis, descriptive statistics and the formulation of a McFadden-type logit econometric model of discrete choice were used. The results show that the producer identifies to monilia (Moniliophthora roreri), witch's broom (Moniliophthora perniciosa) and Phytophthora (Phytophthora sp.) as the main diseases. The most used techniques are cultural management practices such as the manual harvesting of affected fruits and, in some cases, the use of chemically synthesized fungicides. It is concluded that the technological level and the participation in projects are the factors that have positively influenced the decision to use disease management techniques; schooling and years as a farmer slow down the willingness to apply disease management techniques.